Alcoholic drink produced by pea is a risk factor for incident knee surgery in patients with knee osteoarthritis - Huang, Xiaopeng; Zhang, Jinshan; Zheng, Yongqiang; Liu, Xiaofeng; Xu, Yongquan; Fang, Yangzhen; Lin, Zhenyu; Lin, Liang; Zhang, Hongpeng; Wang, Zefeng (Frontiers in Nutrition, 2023)
Objective:To investigate whether alcohol exposure and specific alcoholic drinks are independent risk factors for incident knee surgery in knee osteoarthritis (KOA) patients. Methods: We identified all patients who were clinically diagnosed as KOA between January 2010 and January 2018 in our outpatient department. Demographic, clinical and radiographic data were collected from the database of our hospital. Next, we analyzed the association between alcohol consumption and incident knee surgery. Results: A total of 4341 KOA patients completed the current study and included for the final analysis. Incident knee surgery in purpose of treating osteoarthritis was observed in 242 patients. Incident knee surgery was significantly associated age (OR [95%CI], 1.023 [1.009-1.039], P=0.002), BMI (OR [95%CI], 1.086 [1.049-1.123], P<0.001), baseline K-L grade 3 (OR [95%CI], 1.960 [1.331-2.886], P=0.001), baseline K-L grade 4 (OR [95%CI], 1.966 [1.230-3.143], P=0.005), 7.1-14 drinks per week (OR [95%CI], 2.013 [1.282-3.159], P=0.002), >14 standard drinks per week (OR [95%CI], 2.556 [1.504-4.344], P=0.001) and the most common alcoholic drink produced by pea (OR [95%CI], 3.133 [1.715-5.723], P<0.001).Conclusions: KOA patients who consumed more than 7 standard drinks per week were at substantial risk of incident knee surgery. In addition, alcoholic drink produced by pea is also an independent risk factor.